O enunciado da gestão educacional nas linhas de pesquisa Estudos Culturais em/da Educação dos PPGES da UFPB, ULBRA e UFRGS - Rodrigues, Krislânia Damascena (2024)
Educational management ranges from defining policies and objectives, to implementing strategies to achieve them and evaluating results. In terms of discourse, educational management is also diverse. Located in the Research Line in Cultural Studies of Education - ECE, which have been applied to understand how culture is used in the educational process, this research has the general objective of analyzing the statement of educational management in the ECE Research Lines in Brazil. Justifying the research, in the investigation into the themes and research that circulate between events in the ECE area, it was possible to verify that the statement on educational management does not appear in the titles of the works and in the discussions, exposing a probable gap in the area. Specifically, we seek to map the academic production of the Lines of Research present in the institutional repositories of UFPB, ULBRA and UFRGS, identify the productions that trigger the discourse of educational management and describe and analyze how the statement of educational management is outlined in the lines of ECE in Brazil. This research is qualitative in nature and adopted the Archaeological Discourse Analysis (AAD) proposed by Michel Foucault (2000; 2008) in his work “Arqueologia do Saber” as a theoretical-methodological reference. To achieve the proposed objectives, the study followed the following steps: first, mapping the source texts related to the research; then proceeded to excavate and analyze the discourse area, exploring the statements according to the approach proposed by Alcântara and Carlos (2013). A single work was found, among the 333 productions of the ECE research lines of the PPGEs of UFRGS, UFPB and ULBRA, from 2012 to 2022. Through the analysis and description carried out from the source, we identified four enunciative series that, articulated, weave the statement of educational management in the lines of research, namely: 1. statement series of school management; 2. enunciative series of democratic management; 3. enunciative series of educational governmentality and 4. enunciative series of school culture.